1998
DOI: 10.1074/jbc.273.42.27043
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Evolutionary Significance of Phospholipid Methylation

Abstract: All nucleated mammalian cells synthesize phosphatidylcholine from choline via the CDP-choline pathway. Hepatocytes have a second pathway for the synthesis of phosphatidylcholine, a stepwise methylation of phosphatidylethanolamine, catalyzed by phosphatidylethanolamine N-methyltransferase and encoded by the Pempt gene. We report that when Pempt-deficient mice were fed a choline-deficient diet for 3 days, severe liver pathology occurred apparently due to a lack of phosphatidylcholine biosynthesis. The hepatic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
162
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 219 publications
(171 citation statements)
references
References 23 publications
6
162
1
2
Order By: Relevance
“…Surprisingly, neither the CDPcholine mice (i.e., Pempt Ϫ/Ϫ mice fed the CS diet), nor PEMT mice (i.e., Pempt ϩ/ϩ mice fed the CD diet) showed any overt signs of abnormality, suggesting that inactivation of either of the 2 pathways can be compensated for, at least partially, by the remaining pathway. 4 Nevertheless, in the present study, we identified a liver-specific function, namely the supply of physiological amounts of PC to bile, that cannot be fully compensated for by the PEMT pathway. Although the results clearly illustrate that each of the 2 PC biosynthetic pathways can provide PC for secretion into the bile, the reduced concentration of PC and especially the reduced PC-to-bile acid ratio in gallbladder bile of PEMT mice indicates that, under physiological conditions, the CDP-choline pathway contributes a greater proportion of PC to bile than the PEMT pathway.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Surprisingly, neither the CDPcholine mice (i.e., Pempt Ϫ/Ϫ mice fed the CS diet), nor PEMT mice (i.e., Pempt ϩ/ϩ mice fed the CD diet) showed any overt signs of abnormality, suggesting that inactivation of either of the 2 pathways can be compensated for, at least partially, by the remaining pathway. 4 Nevertheless, in the present study, we identified a liver-specific function, namely the supply of physiological amounts of PC to bile, that cannot be fully compensated for by the PEMT pathway. Although the results clearly illustrate that each of the 2 PC biosynthetic pathways can provide PC for secretion into the bile, the reduced concentration of PC and especially the reduced PC-to-bile acid ratio in gallbladder bile of PEMT mice indicates that, under physiological conditions, the CDP-choline pathway contributes a greater proportion of PC to bile than the PEMT pathway.…”
Section: Discussionmentioning
confidence: 86%
“…Another potential benefit of the PEMT pathway involves its ability to guarantee choline homeostasis, via subsequent catabolism of PE-derived PC, in instances of nutritional choline insufficiency. 4 The contribution of the 2 biosynthetic pathways for bile PC formation has not been clearly resolved, because it was previously not possible to consider each of the 2 PC biosynthetic pathways separately and independently. Available data from past studies do suggest that PC from the CDP-choline pathway, as well as PC originating from PE-methylation, are secreted into bile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed quantitative real-time PCR assays to critically evaluate the relative contributions of the different CCTs to PtdCho production in mouse tissues. The PEMT transcripts were also quantified because this enzyme, in addition to the CCTs, mediates a reaction significant for PtdCho biosynthesis in liver tissue (54). This technique has a linear range of more than 4 orders of magnitude which allows for wide-ranging detection of both high and very low copy number transcripts in a sample, and the probe designs are based on a common hybridization condition optimized for all the transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…The monomeric CHK proteins combine to form the homo-or hetero-dimeric active forms (15) that catalyze the phosphorylation of choline to phosphocholine in the first committed step in the Kennedy pathway (the cytidine diphosphate (CDP)-choline pathway) for the biosynthesis of phosphatidylcholine (PC) (16). PC is the major phospholipid component of the eukaryotic plasma membrane external leaflet (17), an important precursor for many signaling molecules (18), and is thought to be essential for mammalian survival (19,20). The immediate biosynthetic product of CHK, phosphocholine, may also be an important secondary messenger in regulating cell growth signaling and proliferation (21).…”
mentioning
confidence: 99%